Analisis Kebijakan Percepatan Penggunaan Energi Baru dan Terbarukan dengan Menggunakan Perspektif Multiple Streams Framework (MSF) - Putu Febriawan (Journal of Social Contemplativa, 2026)
In response to the contribution of greenhouse gas emissions and climate change, the government enacted Presidential Regulation Number 112 of 2022 concerning the Acceleration of Renewable Energy Development for Electricity Supply. This study aims to analyze the emergence of Presidential Regulation 112/2022 as a policy agenda through the Multiple Streams Framework (MSF) approach. The research employs a qualitative method through literature review and policy document analysis. The findings reveal that the enactment of Presidential Regulation 112/2022 was influenced by the convergence of three policy streams: problem stream, policy stream, and political stream. The problem stream was characterized by the dominance of fossil energy, climate change threats, and inconsistencies in national energy policies. The policy stream was reflected in various energy transition policy alternatives formulated through the National Energy Plan (RUEN) and PLN Electricity Supply Business Plan (RUPTL) 2021–2030. Meanwhile, the political stream was reflected in the dynamics among policy actors, including government support for the energy transition agenda, particularly during Indonesia’s G20 Presidency, while conservative actors such as PLN also emerged. This study also finds that Joko Widodo acted as a policy entrepreneur by utilizing the policy window to encourage the issuance of Presidential Regulation 112/2022.